Early Graft Dysfunction Following Heart Transplant: Prevention and Management. (March 2020) - Subramani, Sudhakar; Aldrich, Aric; Dwarakanath, Sanjay; Sugawara, Ami; Hanada, Satoshi
Heart transplant can be considered as the "gold standard" treatment for end-stage heart failure, with nearly 5.7 million adults in the United States carrying a diagnosis of heart failure. According to the International Society for Heart and Lung Transplantation registry, nearly 3300 orthotopic heart transplants were performed in 2016 in North America. In spite of significant improvements in overall perioperative care of heart transplant recipients for the past few decades, the risk of 30-day mortality remains 5% to 10%, primarily related to early failure of the allograft. Early graft dysfunction (EGD) occurs within 24 hours after transplant, manifesting as left ventricular dysfunction, right ventricular dysfunction, or biventricular dysfunction. EGD is further classified into primary and secondary graft dysfunction. This review focus on describing overall incidences of EGD, potential risk factors associated with EGD, perioperative preventive measures, and various management options.